SEDIMENTOLOGICAL CHARACTERIZATION OF THE PEDOLOGICAL COVER OF CAMAÇARI ECOLOGICAL RESERVATION, CABO DE SANTO AGOSTINHO, PE, NORTHEASTERN BRAZIL - Danielle Gomes da Silva; Antonio Carlos de Barros Corrêa; Williams de Oliveira dos Santos; Pedro Ricardo da Cunha Nóbrega (Sociedade & Natureza)
This paper deals with the issues of environmental impacts derived from the continuousprocess of metropolitan growth, and aims at identifying and analysing the erosive processesoccurring in an area that has been legally designated as an environmental reservation,therefore said to be of strict permanent preservation. This research is focused on theunderstanding of causal relationships that unleash events of environmental disequilibrium,following the illegal systematic removal of the regolith for providing building materials tolocal civil construction entrepreneurs. It was possible to demonstrate the links between thespatial distribution of superficial materials (soils, sediments and regolith) and the level ofstability of distinct geomorphic units, through the use of a morphostratigraphic approach. Thearea portrays a dissected hilly topography, lying within the limits of “Recife MetropolitanArea”, and therefore suffering the consequence of rapid changes in land use, epitomized bythe extensive removal of natural vegetation and exploitation of its deeply lateritized regolith,in spite of being protected by State laws. Deforestation allied to the removal of the deeplyweathered regolith has caused a rearrangement of the area’s morphodynamic units (Tricart,m1977), as shown by both field and lab-work. However, it was found that the diversity of thepedological cover in the area, as a dynamic response of the lithology to the east coasttradewinds tropical climate, commands the distribution of superficial processes, favoring theocurrence of mass movements, intense linear erosion, damming of superficial waterflow,reworking of sub-recent Aeolian sediments and building of coalescing alluvial fans. Finallythe research threw light on the understanding of the linkages between rates ofgemorphological dynamics and soil cover in a costal humid tropical environment.